BLACK CRATER FIRE HITS TOO CLOSE TO HOME. - Stein, Eileen (Public Management (00333611), 2007)
The author reflects on issues related to the Black Crater Fire that hits Oregon. She argues that a backup of the financial systems, critical files and other important documents of the city hall must be provided for any type of damage. The author notes that an emergency plan should be in place, an inventory of important items to preserve should be on hand and a continuity of operations plan should exist. Suggestions on basic preparations during emergencies are offered.